Mitigation of Porosity and Residual Stress on Car Body Aluminum Alloy Vibration Welding: A Systematic Literature Review - Nurul Muhayat; Eko Surojo; Yupiter HP Manurung; Triyono Triyono; Saifudin Saifudin (Automotive Experiences, 2022)
Fatigue resistance is influenced by porosity and residual stress in welded joints. Fatigue failure in some means of transportation is caused by the inability to withstand the load received from the car body and passengers while operating. This study uses a systematic literature review (SLR) method to identify the effect of vibration welding on porosity and residual stress. Vibration can reduce the empty cavity (porosity) and increase the density of the weld. The ultrasonic vibration spot resistance (UVSR) method with 20 kHz on AA6082 is able to reduce residual stress up to 53% and is effective for homogenization of concentrated residual stress up to 57%.